Pengaruh Tingkat Ekspor dan Inflasi Terhadap Nilai Tukar Selama Pandemi Covid-19 di Negara Mayoritas Muslim - Sari, Anggi Novita (Jurnal Ilmiah Ekonomi Islam, 2023)
The influence of Muslim-majority nations' exports and inflation levels on the exchange rate during the Covid-19 pandemic is investigated in this study, where the level of Covid-19 is discovered to be the determining variable for exchange rate movements in Muslim-majority countries. Multiple linear regression was utilized to examine data from April 2020 to October 2022 in this study. Exports, Covid-19, and inflation all had a simultaneous and partial influence on the currency rate in Muslim-majority nations, according to the findings of the analysis.